Antibody quantity versus quality after influenza vaccination - Feng, JingQi (2009)
The correlates for protection against influenza infection are incompletely characterized. We have applied an ELISA strategy that distinguishes antibodies against native viral surface antigens (potentially neutralizing) from antibodies directed against internal and denatured viral proteins (not neutralizing) to three groups of vaccinated subjects: (1) participants in a study of repeated annual vaccination (2) elderly subjects and (3) patients with Systemic Lupus Erythematosus compared to control subjects. Antibody increase after vaccination was inversely related to the level of pre-existing antibodies in all groups; most subjects had significant initial antibody levels and showed little increase in amount of antibody after vaccination, but the avidity of their serum antibodies tended to increase. Antibodies against denatured virus proteins varied with vaccine formulation; vaccines that are more recent have less total protein for the same amount of native hemagglutinin. We propose an index consisting of rank order of antibody level plus antibody avidity, both measured against native virus, plus hemagglutination-inhibition antibody titer, as a useful measure of immunity against influenza.